Histopathological, biochemical and molecular changes of reproductive function after malathion exposure of prepubertal male mice. Issue 18 (5th March 2015) - Selmi, Slimen; Tounsi, Haifa; Safra, Ines; Abdellaoui, Afifa; Ridha Rjeibi, Mohamed; El-Fazaa, Saloua; Gharbi, Najoua
<x xml:space="preserve">Abstract</x> We aimed in the present work to evaluate the implication of oxidative stress in the toxicological effects of subchronic malathion exposure on reproductive function in mice.